Estimação sintética de matrizes origem/destino a partir de contagens volumétricas em áreas com controle do tráfego em tempo real com o auxílio do queensod - Souza, Dante Diego de Moraes Rosado e (2007)
Since 2000, Fortaleza has a modern urban traffic control system (CTAFOR) that, although efficiently reaching its operational objectives in controlling the urban traffic, does not solve all the congestion problems on the network. One way of improving the performance of such a system would be to gather precise information about the travel behavior within the area under control, allowing real time actions and characterizing CTAFOR as a real Intelligent Transportation System (ITS). In such a context, the main objective of this research was to estimate motorized person trips patterns in an area within a region under control of Fortaleza’s UTC system, using a synthetic OD matrix estimation model which is based in traffic flow volumes, running on QueensOD software. As a first step, it was defined the area for the case study, that would be representative of the whole region controlled by CTAFOR, in which this model was applied with the objective of gaining a better understanding and experience in its use. After defining the study area, it was developed the step of calibrating the estimation model regarding the error criteria used to calculate the differences between estimated and observed trip demands, as well as estimated and observed traffic flows. This step was followed by a sensitivity analysis on the estimation results due to the variation in the quality of the input data (OD seed matrix and traffic volumes) and an analysis of the variability of the demand. As the main conclusions, it can be pointed out that the information provided by CTAFOR alone are not enough to estimate good quality OD matrices, requiring good OD seed matrices. Therefore, if one wants to estimate matrices for different periods of the day, it is necessary to collect sample OD matrices directly in the field for each time period, since the use of a seed OD matrix predefines the structure of the OD matrix to be estimated.